FEATURES AND COURSE OF A SEIZURE ATTACK IN CHRONIC ISCHEMIA OF THE BRAIN - Kuranbaeva Satima Razzakovna; Kalandarova Sevara Xujanazarovna (Web of Journals Publishing, 2024)
This article examines the characteristics, progression, and clinical manifestations of seizure attacks in patients with chronic brain ischemia. By analyzing clinical cases and reviewing existing literature, the study identifies specific seizure patterns, frequency, and triggers unique to this condition. It highlights diagnostic approaches and therapeutic strategies to improve management outcomes for patients at risk of seizure attacks in the context of chronic ischemic changes in the brain.
Keywords: Chronic brain ischemia, seizure attack, epilepsy, cerebrovascular disease, ischemic stroke, neurophysiology, diagnostic techniques, treatment strategies.